Estudo de plâncton, particularmente da bioecologia de Temora stylifera (Dana, 1849) (Copepoda, Calanoida) Rio de Janeiro - RJ: emissário submarino de Ipanema e Baía de Guanabara - Schutze, Maria Luisa Motta (1987)
We present a contribution to the knowledge of the Plankton, particularly of the ecobiology of Temora stylifera (Dana, 1849) Copepoda Calanoida, Temoridae family, of the coast of Rio de Janeiro (RJ), Submarine Sewage of Ipanema and Guanabara Bay We make a morphological description of Temora stylifera in its adult stage and in the nauplius and copepodit stages. We study as well the species'biology, annual cycle, generations, biometry and biogeography. The application of enzymatic electrophoresis techniques rendered evident some methodological aspects allowing a better understanding of the Temora stylifera populations. With respect to the plankton, we developped the quantitative aspect, considering the large Phytoplankton groups, chlorophyll a and the pigmentary diversity. Regarding the Zooplankton, we put in relief the importance of the Copepoda. We tried to establish some related points, to find some of the links between the two coastal regions of Rio de Janeiro which undergo the impact of the urban and industrial wastes and the populations there existant. We point out some of their environmental, meteorological and hydrological characteristics. This study is within the Marine Ecosystem research programme being developped by the Santa Ursula University.